2020
DOI: 10.1136/bmjgh-2020-002396
|View full text |Cite
|
Sign up to set email alerts
|

The good and the bad: using C reactive protein to distinguish bacterial from non-bacterial infection among febrile patients in low-resource settings

Abstract: C reactive protein (CRP), a marker for the presence of an inflammatory process, is the most extensively studied marker for distinguishing bacterial from non-bacterial infections in febrile patients. A point-of-care test for bacterial infections would be of particular use in low-resource settings where other laboratory diagnostics are not always available, antimicrobial resistance rates are high and bacterial infections such as pneumonia are a leading cause of death. This document summarises evidence on CRP tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 33 publications
1
52
1
2
Order By: Relevance
“…[22,23] Although the role of CRP was debatable as a biomarker of either inflammation or infection, [7,8] our result affirmed the stand of Escadafal et al (2020) whereby CRP levels correlated with the presence of bacterial infection and was consistent across various studies. [24] Our study showed better performance of CRP than PCT which is comparable to other LMIC context studies in contrary to the observations in high-income countries. [10,23,25] PCT played an essential role in antibiotic stewardship (AMS) and was recognised internationally for both its diagnostic and prognostic properties.…”
Section: Discussioncontrasting
confidence: 81%
“…[22,23] Although the role of CRP was debatable as a biomarker of either inflammation or infection, [7,8] our result affirmed the stand of Escadafal et al (2020) whereby CRP levels correlated with the presence of bacterial infection and was consistent across various studies. [24] Our study showed better performance of CRP than PCT which is comparable to other LMIC context studies in contrary to the observations in high-income countries. [10,23,25] PCT played an essential role in antibiotic stewardship (AMS) and was recognised internationally for both its diagnostic and prognostic properties.…”
Section: Discussioncontrasting
confidence: 81%
“…CRP was chosen as the biomarker for inflammation in this study since it is widely used and affordable worldwide, it is correlated with serum IL-6 concentrations, and early clinical studies of COVID-19 had reported it to be associated with severity and prognosis, with a value of greater than 50 mg/L associated with severe disease and a concentration of around 75 mg/L distinguishing fatal from non-fatal cases. 23 , 24 , 25 , 26 , 27 , 28 Whether hypoxic patients with a CRP of less than 75 mg/L could benefit from tocilizumab is unknown. There are some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…CRP was chosen as the biomarker for inflammation in this study since it is widely used and affordable worldwide, it is correlated with serum IL-6 levels, and early clinical studies of COVID-19 had reported it to be associated with severity and prognosis, with a value of >50 mg/L associated with severe disease and a level of around 75 mg/L distinguishing fatal from non-fatal cases. [23][24][25][26][27][28] Whether hypoxic patients with a CRP <75 mg/L could benefit from tocilizumab is unknown. Further work is also needed to consider the health economic benefits of tocilizumab and related IL-6 inhibitors in terms of both patient outcomes and usage of healthcare resources (duration of hospital stay, and frequency of invasive mechanical ventilation and renal replacement therapy).…”
Section: Discussionmentioning
confidence: 99%